Exploring the effects of Xinnaoning capsule in microcirculatory dysfunction model rats through laser speckle contrast imaging and metabolomics - Sun, Yuanfang; Li, Shasha; Du, Lijing; Ren, Xiaopeng; Jin, Huizi; Yan, Shikai; Xiao, Xue (Frontiers in Pharmacology, 2025)
BackgroundMicrocirculatory dysfunction leads to a number of diseases and worsen prognosis. Blood-activating drugs like Xinnaoning capsule may improve circulation, but its pharmacological effects in microcirculatory dysfunction remain unclear.ObjectiveThe purpose of this study is to determine the pharmacological effect of Xinnaoning capsules in treating microcirculatory dysfunction.MethodsAdrenaline and icy water stimuli were used to establish a rat model of acute microcirculatory dysfunction. Detecting laser speckle contrast imaging, coagulation function, hemorheology, and the Elisa assay were conducted to investigate the effect of Xinnaoning capsule on microcirculation in rats. In addition, the untargeted metabolomics was applied to character the therapeutic effect of Xinnaoning systematically from the perspective of endogenous terminal metabolites.ResultsLaser speckle contrast imaging showed that model rats suffered low perfusion in ears, feet and tails, and Xinnaoning capsule treatment increased microcirculatory blood flow. Xinnaoning capsule diminished the reduction of thrombin time, prothrombin time, activated partial thromboplastin time and the elevated fibrinogen level caused by acute microcirculatory dysfunction. Xinnaoning capsule could recover the increased blood viscosity as well as the abnormal vasomotor and microcirculation function in model rats. Furthermore, Xinnaoning capsule intervention could alter metabolic state in model rats, which was characterized by the abnormality metabolites mainly in pathway of phospholipids and arachidonic acid metabolism.ConclusionThe macroscopic image and microscopic indicators elucidated that Xinnaoning capsule was highly effective against microcirculatory dysfunction. The present study provided a new perspective on the clinical application of Xinnaoning capsule, and contributed to explore novel therapeutic drug against microcirculatory dysfunction.